(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
The paper analyzes and describes continuities of authoritarian regimes in Africa since the return to multipartism by classifying cases which have been stable in the authoritarian form in the last thirty years. Special attention is devoted to political successions, whether these are ruled by a party and/or the military or took the form of dynastic ones. In particular, the existence of collegial control on personal power is presented as an important way of ensuring continuities of party and/or military hegemony over the authoritarian regime. Collegial control may also strengthen the stability of the regime in its authoritarian form. However, it is not excluded that a moderate degree of personal power may also be helpful in ensuring stability if combined with collegial control as it helps in limiting factionalism.